2014
DOI: 10.3892/mmr.2014.2597
|View full text |Cite
|
Sign up to set email alerts
|

Low-magnitude high-frequency loading, by whole-body vibration, accelerates early implant osseointegration in ovariectomized rats

Abstract: Osteoporosis deteriorates jaw bone quality and may compromise early implant osseointegration and early implant loading. The influence of low-magnitude, high-frequency (LMHF) vibration on peri-implant bone healing and implant integration in osteoporotic bones remains poorly understood. LMHF loading via whole-body vibration (WBV) for 8 weeks has previously been demonstrated to significantly enhance bone-to-implant contact, peri-implant bone fraction and implant mechanical properties in osteoporotic rats. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Application of varying frequencies of LIV signal (0.075-0.3 g, 12-150 Hz, 5 min/day -1-4 weeks) had beneficial impact on bone recovery at the implant site as well as increased bone to implant contact (Ogawa et al, 2014). Not only effective for the osseointegration of implants during healthy conditions, but in an osteoporotic (OVX) rat model for osseointegration application of LIV signals (0.2 g, 45 Hz, 30 min/day -4 weeks) improved the healing significantly (Liang et al, 2014). In a similar study, hydroxyapatite coated titanium screws in the tibia of rats were exposed to LIV (0.3 g, 40 Hz, 30 min/day -12 weeks), and mechanical signals enhanced osteoblast differentiation, extracellular matrix synthesis, and mineralization together with an increase in bone mass and reduction in bone resorption (Zhou et al, 2015).…”
Section: Effect Of LIV Signals On Implant Osseointegrationmentioning
confidence: 97%
“…Application of varying frequencies of LIV signal (0.075-0.3 g, 12-150 Hz, 5 min/day -1-4 weeks) had beneficial impact on bone recovery at the implant site as well as increased bone to implant contact (Ogawa et al, 2014). Not only effective for the osseointegration of implants during healthy conditions, but in an osteoporotic (OVX) rat model for osseointegration application of LIV signals (0.2 g, 45 Hz, 30 min/day -4 weeks) improved the healing significantly (Liang et al, 2014). In a similar study, hydroxyapatite coated titanium screws in the tibia of rats were exposed to LIV (0.3 g, 40 Hz, 30 min/day -12 weeks), and mechanical signals enhanced osteoblast differentiation, extracellular matrix synthesis, and mineralization together with an increase in bone mass and reduction in bone resorption (Zhou et al, 2015).…”
Section: Effect Of LIV Signals On Implant Osseointegrationmentioning
confidence: 97%
“…For example, in studies to use vibration exposure for promoting bone growth or maintenance, there were acceleration ranges between 2.94 and 29.43 m/s 2 , frequency ranges between 8 and 90 Hz, varied durations of exposure, as well as animal age and species . Higher magnitude WBV of 19.62 and 29.43 m/s 2 was only osteogenic in ovariectomized rats, (p316) whereas low magnitude vibration applied to osteoporotic (ovariectomized) rats at approximately 2 m/s 2 reversed some of the negative effects of osteoporosis and accelerated early peri‑implant osseointegration . An evaluation of WBV effects on bone formation in healthy rats using a constant acceleration and 45 or 90 Hz demonstrated that only a frequency of 90 Hz stimulated bone formation, indicating that studies performed only at the low frequencies would have yielded a different conclusion regarding the effects of vibration.…”
Section: Challenges In Animal Study Designmentioning
confidence: 99%
“…Considering small animal models, mechanical stimulation can be (a) applied directly to the implant through miniaturized devices, (b) administered to the single implanted bone through loads coming from adjacent bones or joints, and (c) delivered through generalized whole body vibrations. Figures modified from with permission.…”
Section: Effect Of Mechanical Loading On Bone Regenerationmentioning
confidence: 99%
“…The application of WBV is relatively straightforward but its mechanisms of action at tissue and cellular level are less understood. The effect of mechanical stimulations on bone regeneration in the form of low (∼1–10 Hz) or high (∼10–100 Hz) frequency vibrations have been investigated in animal models . Ogawa et al placed titanium screws in the proximal tibiae of rats and applied daily (5 days a week) WBV starting immediately after implantation.…”
Section: Effect Of Mechanical Loading On Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation